Clinical and radiographic features of psittacosis infection. Issue 7 (July 1985) - Coutts, I I; Mackenzie, S; White, R J
Abstract : Forty three cases of psittacosis infection were identified retrospectively over a five year period. The commonest clinical presentation was of a bronchitic illness with a productive cough and features of systemic upset. In 12 (28%) cases no radiographic abnormality was detected on the chest film. Segmental shadowing was the commonest abnormality but lobar and more extensive consolidation occurred. There were no radiographic features that allowed confident differentiation from other causes of pneumonia. The total and differential white cell counts were usually normal and this feature may help to differentiate psittacosis from bacterial pneumonia.